1984
DOI: 10.1007/bf00042732
|View full text |Cite
|
Sign up to set email alerts
|

The response of a confined gas to a thermal disturbance: rapid boundary heating

Abstract: Summa~An inert compressible gas confined between infinite parallel planar walls is subjected to significant heat addition at the boundaries. The wall temperature is increased during an interval which is scaled by the acoustic time of the container, defined as the passage time of an acoustic wave across the slab. On this time scale heat transfer to the gas occurs in thin conductive boundary layers adjacent to the walls. Temperature increases in these layers cause the gas to expand such that a finite velocity ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Rayleigh [1] first approached the idea that a slight variation in temperature can create a mechanical reaction in the form of an acoustic wave in the rest of the fluid. The resulted fluid motion from rapid heating, termed as thermoacoustic convection [2], was numerically investigated by Ozoe et al Through use of matched asymptotic expansions and multiple-time-scale technique, Kassoy [3] and Radhwan and Kassoy [4] conducted pioneering studies on the thermoacoustic interaction in a confined perfect gas under slow and rapid boundary heating. Their results showed that the process is dominated by two physical regimes, which feature, respectively, thermomechanical convection on the acoustic timescale, and strong conductive-convective coupling on the typical timescale of thermal diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Rayleigh [1] first approached the idea that a slight variation in temperature can create a mechanical reaction in the form of an acoustic wave in the rest of the fluid. The resulted fluid motion from rapid heating, termed as thermoacoustic convection [2], was numerically investigated by Ozoe et al Through use of matched asymptotic expansions and multiple-time-scale technique, Kassoy [3] and Radhwan and Kassoy [4] conducted pioneering studies on the thermoacoustic interaction in a confined perfect gas under slow and rapid boundary heating. Their results showed that the process is dominated by two physical regimes, which feature, respectively, thermomechanical convection on the acoustic timescale, and strong conductive-convective coupling on the typical timescale of thermal diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The problem of unsteady heating has been studied in the context of continuum gas dynamics in a series of papers 6,7 under the assumption of gradual changes in wall thermal states. To satisfy the continuum assumption, a heating time scale longer than some modest multiple of the molecular collision time has been assumed.…”
Section: Introductionmentioning
confidence: 99%
“…A more systematic approach to thermomechanical problems involving transient, spatially resolved heat addition and the mechanical waves generated subsequently by localized gas expansion has been developed by Kassoy and co-workers (e.g., [18,19], [26][27][28][29][30]). Asymptotic procedures are used to identify equations that describe energy addition on explicit time scales to finite gas volumes, and the resulting gasdynamic waves.…”
mentioning
confidence: 99%